Effect of Kersen Leaf (Muntingia calabura) Ethyl Acetate Extract on Blood Uric Acid Levels - Dezmonda, Raynalda Chriesmart; Ediningsih, Endang (Nexus Biomedika, 2017)
Introduction: Kersen leaves are known to contain various kinds of active substances one of which is a flavonoid, a type of flavonoid that is quersetin have a Â function as lowering uric acid levels through inhibition of the enzyme xanthine oxidase. This study aims to find out Kersen leaves (Muntingia calabura) Ethyl Acetate Extract Effect on Blood Uric Acid Levels in Mice (Mus muculus) Male with Hyperuricaemia Model. Methods: This study was an experimental laboratory with post test only control group design. A sample of male mice, aged 2-3 months, body weight Â± 25-40 grams. The subjects were male mice 24 individuals, were divided into six groups randomly. Group I as normal control, group II as negative control received caffeine 0.42 mg and 0.5ml chicken liver juice orally. Group III, IV, V and VI received respectively allopurinol treatment 0.2 mg (positive control), kersen leaf extract consecutive doses 12.74 mg, 25.48 mg and 50.96 mg it orally, and induced caffeine 0.42 mg and chicken liver juice 0.5ml orally 1 hour after treatment. Measurement of uric acid levels using a GCU test strip, blood was taken from the mice tail one hour after the induction of hyperuricemia. Data were analyzed using one-way ANOVA followed post hoc LSD test Results: The result showed blood uric acid levels throughout the test animals was significantly different (pâ¤0.05). The test results, post hoc LSD test showed that the positive control group and group IV, V and VI significantly different from the negative groups (pâ¤0.05) while there was a significant difference in the group IV, V and VI (p â¥ 0.05) with the normal control group and positive control group. Conclusion: All doses can lower uric acid levels of mice significantly. And all three doses did not differ significantly of uric acid levels compare to therapeutic doses of allopurinol. Keywords: Kersen leaves, uric acid, allopurinol, caffeine, quercetinÂ